Talking placebo: a qualitative study of patients’ attitudes toward open-label placebo implementation into clinical practice - Frey Nascimento, Antje; Bakis, Berfin; Gaab, Jens; Schneider, Tobias; Papadopoulou, Athina; Ritter, Milena; Bernstein, Michael H.; Blease, Charlotte R.; Locher, Cosima (Frontiers in Psychology, 2025)
BackgroundFor more than a decade, studies have supported the efficacy and safety of placebos without deception—so-called open-label placebos (OLPs)—to harness placebo effects in primary care while aligning with key ethical principles. Since treatment acceptance, feasibility, and successful implementation of novel interventions into clinical practice depend on patients’ attitudes, patients’ perspectives, perceived obstacles, and ideas on OLP use in clinical practice have yet to be elucidated. Therefore, patient and public involvement is increasingly demanded in research and its implementation into clinical practice. Qualitative research offers a unique opportunity to comprehensively understand attitudes, expectations, perceived benefits, and barriers from a patient’s point of view. Thus, we studied patients’ attitudes, concerns, and ideas toward OLP implementation into clinical practice with focus group discussions (FGDs).MethodsIn 2022, three exploratory online FGDs, each including two patients with the same condition, were conducted with adult patients affected by chronic back pain (n = 2), chronic migraine (n = 2), or chemotherapy-induced emesis/nausea (n = 2). Physicians recruited participants in three outpatient clinics at the University Hospital Basel in Switzerland. The FGDs were held online for 60 min. Qualitative data was analyzed using Reflexive Thematic Analysis, applying an inductive-deductive hybrid approach within a social constructivist framework.ResultsIn total, five semantic-latent subthemes were identified, entailing: (i) Placebos: Promising but risky; (ii) Acceptance of OLPs depends on a myriad; (iii) Be trustworthy, but deception may be necessary; (iv) Harnessing placebo effects without placebos; (v) From bench to bedside: Clinical transference of OLPs. The themes reflect an in-depth discussion of the usage of OLPs in the clinical context, accompanied by different ambivalences regarding implementation, prerequisites, and the provider role.ConclusionThe FGDs provided insights into distinct attitudes, concerns, varying acceptance, and patients’ ideas regarding the clinical implementation of OLP interventions. While some patients displayed high acceptance, several concerns regarding ethical and practical issues have been expressed. OLP acceptance and attitudes toward practical issues of OLP intake differed between groups and within the same clinical condition.Trail registrationClinicalTrials.gov, identifier NCT05166213.